Computer Aided Verification 25th International Conference, CAV 2013, Saint Petersburg, Russia, July 13-19, 2013, Proceedings - Sharygina, Natasha; Veith, Helmut (Theoretical Computer Science and General Issues, 2013)
This book constitutes the thoroughly refereed proceedings of the 25th International Conference on Computer Aided Verification, CAV 2013 held in St. Petersburg, Russia in July 2013. The 54 regular and 16 tool papers presented were carefully selected from 209 submissions. The papers are organized in topical sections on biology, concurrency, hardware, hybrid systems, interpolation, loops and termination, new domains, probability and statistics, SAT and SMZ, security, shape analysis, synthesis, and time.